The corrosion characteristics and mechanism of directionally solidified Mg-3Zn-xCa alloys - Zhang, Yi; Feng, Xiaohui; Huang, Qiuyan; Li, Yingju; Hao, Xuehui; Wang, Changzheng; Yang, Yuansheng (Journal of magnesium and alloys, 2023)
An investigation into the corrosion characteristics and mechanism of directionally solidified (DSed) Mg-3Zn-xCa (x = 0, 0.2, 0.5, 0.8 wt.%) alloys in 0.9 wt.% NaCl solution is presented. The DSed microstructure consists of columnar dendrites and eutectics distributed in the interdendritic region. The primary dendritic arm spacing (PDAS) and the volume fraction (fv) of the secondary phases are under the significant impact of the content of Ca. The corrosion rates evaluated using electrochemical measurements and immersion tests are accelerated monotonously with the increase of Ca content in DSed alloys. The corrosion resistance of the DSed alloys is significantly affected by the corrosion products film (CPF) and the secondary phases. The corrosion products of DSed Mg-3Zn alloy contain Mg(OH)2 and ZnO. The existence of ZnO greatly enhances the corrosion resistance of DSed Mg-3Zn alloy. As for the DSed alloys containing Ca content, a relatively protective CPF without deep pits can form on the surface of DSed Mg-3Zn-0.2Ca specimen during the corrosion. The fv of the secondary phases dominates the corrosion rate of the DSed Mg-Zn-Ca alloys. The corrosion of DSed Mg-3Zn-xCa alloys initiates as a result of micro-galvanic coupling between the cathodes of secondary phases and α-Mg matrix anode. Then, the corrosion gradually extends longitudinally with the breakdown of CPF.